2005
DOI: 10.1093/jb/mvi172
|View full text |Cite
|
Sign up to set email alerts
|

Link between the Ubiquitin Conjugation System and the ISG15 Conjugation System: ISG15 Conjugation to the UbcH6 Ubiquitin E2 Enzyme

Abstract: ISG15 is a ubiquitin-like protein that is upregulated on treatment with interferon. ISG15 is considered to be covalently conjugated to cellular proteins through a sequential reaction similar to that of the ubiquitin conjugation system consisting of E1/E2/E3 enzymes: UBE1L and UbcH8 have been reported to function as E1 and E2 enzymes, respectively, for ISG15 conjugation. Several cellular proteins have been identified as targets for ISG15 conjugation, but the roles of ISG15 conjugation remain unclear. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…19,20) All constructs were verified by DNA sequencing. To generate the expression plasmids, the respective PCR fragments were subcloned into pCI-neo-6His, pCI-neoC3Flag, pCI-neo-3T7, pCI-neo-5HA, and pCI-neo-2S vectors that had been generated by inserting oligonucleotides encoding a histidine tag sequence (6His), three repeats of a Flag tag sequence, three repeats of a T7 tag sequence, five repeats of an HA tag sequence, and two repeats of an S peptide sequence, respectively, into the pCI-neo mammalian expression vector (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20) All constructs were verified by DNA sequencing. To generate the expression plasmids, the respective PCR fragments were subcloned into pCI-neo-6His, pCI-neoC3Flag, pCI-neo-3T7, pCI-neo-5HA, and pCI-neo-2S vectors that had been generated by inserting oligonucleotides encoding a histidine tag sequence (6His), three repeats of a Flag tag sequence, three repeats of a T7 tag sequence, five repeats of an HA tag sequence, and two repeats of an S peptide sequence, respectively, into the pCI-neo mammalian expression vector (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…To measure the level of TRAF6 polyubiquitination, the supernatant was alternatively subjected to affinity-purification with S-protein-immobilized agarose beads and the purified proteins were subjected to Western blotting with the indicated antibodies. The following antibodies were used: rabbit anti-S peptide (Santa Cruz), mouse anti-Flag tag M2 (Sigma), mouse anti-T7 tag (Novagen), mouse anti-polyubiquitin (FK2), 21) rabbit anti-ISG15, 19) mouse anti-Ubc13 (Zymed), and rabbit antiactin (Sigma) antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The mammalian expression plasmids of ISG15, UBE1L, and UbcH8 were generated as described previously [15]. The open-reading frames of human XPD (ERCC2), STK38, RGS3 isoform 1, α-tubulin, and Herc5 were amplified by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of ISG15 is induced by interferon stimulation and ISG15 is conjugated to various cellular proteins (ISGylation) in a manner similar to ubiquitination that is catalyzed by the sequential action of E1 (ubiquitin-activating enzyme), E2 (ubiquitin-conjugating enzyme) and E3 (ubiquitin ligase) [4,5]. Target proteins modified with ISG15 [6][7][8], the E1 (UBE1L) and E2 (UbcH8) enzymes functioning in ISGylation [9][10][11], and a de-ISGylating enzyme (UBP43) [12] have been identified, but biological consequences of ISGylation have been studied in only a few cases [13][14][15]. Recently, Efp and Herc5 have been reported to function as E3 ligases for ISGylation [16,17], but there seems to be a difference in function between Efp and Herc5 because Herc5, but not Efp, influences the ISGylation status of whole cellular proteins [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Using the siRNA approach, it has been shown that UbcH8 is a predominant ISG15 E2 for IFN-induced protein ISGylation in HeLa cells. Interestingly, an ISG15 thioester intermediate was also detected with UbcH6, suggesting that UbcH6 would be another ISG15 conjugating enzyme [17]. We separately tested the effect of UbcH8 and UbcH6 on the ISGylation of EFP.…”
Section: Ubch6 and 8 Can Support The Isgylation Of Efpmentioning
confidence: 99%